ZEB1 as a marker of metastasis in thyroid carcinomas: review of literature and own data - P.P. Zinych; V.M. Pushkarev; N.I. Levchuk; M. Tronko (Mìžnarodnij Endokrinologìčnij Žurnal)
Metastases are the leading cause of death from malignant tumors. The metastatic process involves the exit of cancer cells from the primary tumor into the blood or other transport system, colonization and proliferation in a distant organ. The key process of the metastatic cascade is the epithelial-mesenchymal transition (EMT), which consists in the transformation of epithelial cells into mesenchymal, capable for migration. At the same time, epithelial markers (E-cadherin) are replaced by mesenchymal ones (N-cadherin, vimentin, fibronectin). In malignant tumors, EMT is initiated by different signaling pathways through the regulation of transcription factors (EMT-TFs) and miRNAs. Downregulation of E-cadherin expression is induced by transforming growth factor β, epidermal growth factor, fibroblast growth factor, and interleukin-6. Growth factors activate intracellular signaling pathways, which in turn induce several repressors of E-cadherin gene transcription, such as Snail, Slug, zinc finger E-box binding homeobox 1 (ZEB1), ZEB2, Twist, TBX-2, and SIX. ZEB1 is the main EMT-TF of the ZEB family and is associated with cellular plasticity, dissemination, and the switch from a dormant to proliferative phenotype at distant metastatic sites and is a determinant of poorer clinical prognosis in most human cancers. ZEB1 is at the forefront of transcription factors involved in the EMT control and promotes tumor cell migration and diffusion, cell stemness, resistance to treatment, metastasizing and evasion of the immune response. Since ZEB1 is a key regulator of EMT, metastasizing is associated with cancer stem cell formation and resistance to therapy in many cancers, including papillary thyroid carcinoma. It may be an important marker of tumor invasiveness. Preoperative examination of its level in blood cells and plasma in thyroid carcinomas can help in determining the extent of surgical intervention and subsequent radioiodine therapy.